PAKAIAN DAN KAIN (JENIS, BAHAN PEMBUAT, DAN PEWARNA) PADA KERAJAAN MATARAM KUNA PERIODE JAWA TENGAH ABAD IX-X M - Setyawan, Hari (Naditira Widya, 2007)
Cloth varieties has been known in Mataram Kingdom since IX-X century AD. Some evidences for clothes varieties can be found in several ancient Javanese inscriptions, ancient Kakawin, Chinesesource, or temple relief. This paper presents cloth varieties, different professions in cloth making, varieties of plant for colouring cloth and fibre used. The results of recent research about varieties of plant species as sources of fibre for making cloth and substances used in colouring process are good comparation data to support interpretation.